Facts About Minerals - R. Elaine Turner; Wendy J. Dahl (EDIS)
If the word “mineral” makes you think of rocks, you’re right! Minerals are substances like calcium, phosphorus, iron, and zinc that are found in rocks and the soil. They also are needed for optimal nutrition. There are 16 different minerals that are known to be needed in our diets. Several other minerals may be needed in very small amounts. It’s important to eat a variety of foods from each of the food groups in order to get all the minerals in your diet. This revised 3-page fact sheet was written by R. Elaine Turner and Wendy J. Dahl, and published by the UF Department of Family, Youth and Community Sciences, January 2012.